Meningkatkan Literasi Keuangan Melalui Digitalisasi Pencatatan Keuangan Untuk UMKM (Toko Permata Almina Medan) - Desmon Gunadi Siagian; Andreas Panjaitan; Debora Silvia Hutagalung; Artha Putri Br. Karo; Yohana Yulianti Simbolon (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2025)
This community service activity aimed to improve financial literacy among Micro, Small, and Medium Enterprises (MSMEs) through the digitalization of financial record-keeping at Toko Permata Almina, located in Pusat Pasar Medan. The activity was conducted on May 10, 2025, using a training approach focused on basic financial literacy and the use of the Tokoku digital bookkeeping application. The results showed a significant increase in participants' understanding of the importance of systematic financial recording. Participants were able to use the Tokoku application to record daily transactions and acknowledged the benefits of automatic financial reports provided by the application for analyzing business performance. Furthermore, participants experienced higher efficiency compared to manual recording methods. Overall, this activity positively impacted the enhancement of digital skills and supported data-driven business decision-making.